2022
DOI: 10.3389/fcimb.2022.1047351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Bacillus amyloliquefaciens on the growth, immune responses, intestinal microbiota composition and disease resistance of yellow catfish, Pelteobagrus fulvidraco

Abstract: The influence of dietary probiotic Bacillus amyloliquefaciens on the growth performance, digestive enzyme activity, immune parameters and disease resistance of yellow catfish (Pelteobagrus fulvidraco) was evaluated. Commercial diet (C) or diet containing 106 cfu/g B. amyloliquefaciens (T) was fed for 4 weeks, and final weight (FW), specific growth rate (SGR) and feed conversion ratio (FCR) were improved (p<0.05) in the T group. Dietary B. amyloliquefaciens increased protease and amylase activities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…In this study, we aimed to investigate the effect of Lactobacillus plantarum fermented feed and fermented liquid on the intestinal microbiota of T. fulvidraco by observing the microbiota in different segments of the intestine. Firmicutes, Fusobacteriota, Proteobacteria, and Bacteroidota were the four dominant phyla in the intestine, regardless of diet and intestinal segment, which was consistent with previous research about T. fulvidraco [26,54]. Among these dominant phyla, Proteobacteria are well adapted to survive in the fish intestine and aquatic environment, and they contribute to significant host functions such as nutrition [55].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we aimed to investigate the effect of Lactobacillus plantarum fermented feed and fermented liquid on the intestinal microbiota of T. fulvidraco by observing the microbiota in different segments of the intestine. Firmicutes, Fusobacteriota, Proteobacteria, and Bacteroidota were the four dominant phyla in the intestine, regardless of diet and intestinal segment, which was consistent with previous research about T. fulvidraco [26,54]. Among these dominant phyla, Proteobacteria are well adapted to survive in the fish intestine and aquatic environment, and they contribute to significant host functions such as nutrition [55].…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have suggested that Cetobacterium is a potentially beneficial microbiota for fish [57,58]. Most studies proposed that the proportion of Cetobacterium in intestinal microbiota increased after some probiotics were applied, including Bacillus and Enterococcus [26,59,60]. Interestingly, the opposite result was observed with a significant decrease in the Cetobacterium ratio in the foreintestine when feeding a diet fermented with Lactobacillus plantarum, which was consistent with Standen's study showed that in tilapia fed a mixture of multiple probiotics, including Lactobacillus reuteri and Enterococcus faecium, the percentage of Cetobacterium decreased from 13.80% to 0.02% [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained supernatant was used for subsequent enzyme activity determination. Based on the Bradford method, bovine serum albumin (BSA) was used as the standard to determine the total intestinal protein content [ 36 ]. Each group of samples was repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, studies [ 13 , 20 , 23 , 24 , 25 , 26 , 27 ] have exhibited enhancements in the production of enzymes, such as protease and lipase, due to genetic engineering. Other research [ 28 , 29 ] has focused on the bacterium’s potential in plant disease control and its role in promoting plant growth. The wide range of applications and the potential for further improvements underline the importance of ongoing research and development.…”
Section: Genetic Manipulation Of Bacillus Amyloliquefaciensmentioning
confidence: 99%